A 10-Year Follow-Up of Different Intra-Radicular Retainers in Teeth Restored with Zirconia Crowns - Calabro DE; Kojima AN; Gallego Arias Pecorari V; Helena Coury Saraceni C; Blatz MB; Özcan M; Mikail Melo Mesquita A (Dove Medical Press, 2019)
Debora E Calabro,1 Alberto N Kojima,2 Vanessa Gallego Arias Pecorari,3 Cintia Helena Coury Saraceni,3 Markus B Blatz,4 Mutlu Özcan,5 Alfredo Mikail Melo Mesquita1 1Department of Prosthodontics, Paulista University (UNIP) São Paulo, São Paulo, Brazil; 2Department of Dental Materials and Prosthodontics, Paulista State University (UNESP) São José, São Paulo, Brazil; 3Department of Dental Materials, Paulista University (UNIP), São Paulo, Brazil; 4Unit Center for Dental and Oral Medicine Clinic for Fixed and Removable Prosthodontics and Dental Material Science, University of Zurich, Zurich, Switzerland; 5Professor, Department of Preventive and Restorative Sciencie, University of Pennsylvania, Philadelphia, PA, USACorrespondence: Debora E CalabroDepartment of Prosthodontics, Paulista University, Rua Diogo Jacome, 50 - Moema, São Paulo CEP 04512-000, BrazilEmail deboracalabro@doctor.comPurpose: To evaluate the survival rate in restored teeth with three different types of retainers prior to the fixing of crowns with zirconia through this retrospective clinical study. It is unclear how the type of post and core rehabilitation, and type of resin cement affect the longevity of teeth restored with crowns.Methods: In a private clinic, a total of 101 retainers installed by the same professional between June 2008 and January 2018, with an average time of 58.2 months (4.8 years), were analyzed regarding the following factors: survival, cement and failure type. Three types of retainers were used according to the indications found in the literature: filling with Z250 light-cured composite resin, 22 elements; fiberglass post with Z250 light-cured composite resin, 45 elements; and cast metallic core in silver-tin alloy, 34 elements. The retainers were cemented with chemically cured cement, U100, U200, or Panavia F.Results: Data were subjected to Kaplan-Meier analysis (p=0.495). Although the study presented several limitations, no significant differences were observed in the success rates between the types of intra-radicular retainers and the type of cement. The success rates were as follows: metal core, 97.1%; fiberglass post, 95.6%; and filling, 100%. On average, failures occurred at 48.4 months.Conclusion: In view of the results, it is possible to conclude that the different retainers evaluated have similar survival rates.Keywords: fiberpost, type of retainer, cast metallic core, filling core, survival rate